2020
DOI: 10.16899/jcm.797615
|View full text |Cite
|
Sign up to set email alerts
|

Basit Bir Tam Kan Sayımı Gestastonel Diyabetes Mellitusu Öngörebilir Mi?

Abstract: To assess the role of simple complete blood count (CBC) in prediction of gestational diabetes (GDM). Material and Method: Pregnant women screened for GDM in 24-28 gestational weeks with a 75g-OGTT between January 2018-January 2020 were retrospectively investigated. Patients with a known systemic disease, using aspirin, low-molecular-weight heparin and steroids were excluded. A total of 359 patients (81 with GDM and 278 controls) were enrolled. The assessed parameters in CBC were hemoglobin, hematocrit, red blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, IG% values were statistically significantly different between the GDM and control groups (p=0.002). To the best of our knowledge, the study by Aytan et al [16] was the first to evaluate the IG% value in GDM patients. This marker has been reported to increase before conventional markers in inflammatory conditions [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, IG% values were statistically significantly different between the GDM and control groups (p=0.002). To the best of our knowledge, the study by Aytan et al [16] was the first to evaluate the IG% value in GDM patients. This marker has been reported to increase before conventional markers in inflammatory conditions [15].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of immature granulocytes (IG%) is an inflammatory marker seen in complete blood count. It has been reported that in inflammatory conditions, it rises much earlier than conventional parameters such as CRP [15,16]. Although some studies have found no association between GDM and %IG [17], there are still not enough studies on this topic.…”
Section: Introductionmentioning
confidence: 99%